2022
DOI: 10.1002/brb3.2766
|View full text |Cite
|
Sign up to set email alerts
|

Poor expression of miR‐195‐5p can assist the diagnosis of cerebral vasospasm after subarachnoid hemorrhage and predict adverse outcomes

Abstract: Objective: Patients with spontaneous subarachnoid hemorrhage (SAH) may develop refractory arterial cerebral vasospasm (CVS), which is the leading cause of death in SAH patients. This study explored the clinical diagnostic value of serum miR-195-5p levels in CVS after SAH (SAH + CVS) and its relationship with the prognosis of SAH + CVS. Methods: A total of 110 patients with spontaneous SAH were divided into the SAH group (N = 62) and SAH + CVS group (N = 58), with 60 healthy subjects as controls. The clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…MiRNAs play a crucial role in controlling gene expression, including genes involved in SAH, which can lead to both overexpression and under expression of target genes [ 41 ]. Studies have also shown that low expression of miR-195-5p is linked to cerebral vasospasm and poor outcomes in SAH patients [ 75 ]. In other studies, low levels of miR-630 in the CSF were associated with better endothelial function after SAH [ 76 ].…”
Section: Microrna and Sah Prognosismentioning
confidence: 99%
“…MiRNAs play a crucial role in controlling gene expression, including genes involved in SAH, which can lead to both overexpression and under expression of target genes [ 41 ]. Studies have also shown that low expression of miR-195-5p is linked to cerebral vasospasm and poor outcomes in SAH patients [ 75 ]. In other studies, low levels of miR-630 in the CSF were associated with better endothelial function after SAH [ 76 ].…”
Section: Microrna and Sah Prognosismentioning
confidence: 99%
“…MiR-NAs play a crucial role in controlling gene expression; including genes involved in SAH, which can lead to both overexpression and underexpression of target genes 41 . Studies have also shown that low expression of miR-195-5p is linked to cerebral vasospasm and poor outcomes in SAH patients 75 . On the other hand, in other studies low level of miR-630 in the CSF were associated with better endothelial function after SAH 76 .…”
Section: Microrna and Sah Prognosismentioning
confidence: 99%